The Lived Experience of Adult Cancer Survivors After Hematopoietic Stem Cell Transplantation: A Qualitative Study From Saudi Arabia - Almutairi H; Aboshaiqah A; Alzahrani M; Almutairi AF; Salam M (Patient Preference and Adherence)
Hamdan Almutairi,1,2 Ahmad Aboshaiqah,2 Mohsen Alzahrani,3 Adel F Almutairi,4 Mahmoud Salam5 1Transfusion Medicine Services, Department of Pathology and Laboratory Medicine, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 2College of Nursing, King Saud University, Riyadh, Saudi Arabia; 3Division of Hematology and Stem Cell Transplant, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia; 4King Abdullah International Medical Research Center, Riyadh, Saudi Arabia, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 5Alice Ramez Chagoury School of Nursing, Lebanese American University, Byblos, LebanonCorrespondence: Hamdan Almutairi, Transfusion Medicine Services, Department of Pathology and Laboratory Medicine, King Abdulaziz Medical City, Ministry of National Guard Health Affairs, Riyadh, Saudi Arabia, Tel +966503414140, Email MotairiH@mngha.med.sa Mahmoud Salam, Alice Ramez Chagoury School of Nursing, Lebanese American University, Byblos, Lebanon, Tel +96170054397, Email mahmoud.salam@lau.edu.lbBackground: Hematopoietic stem cell transplantation (HSCT) is a high-intensity treatment with the potential to extend the life expectancy of some patients with cancer. The aim of this study is to explore the lived experience of cancer survivors who underwent HSCT from Saudi Arabia.Material And Methods: This study adopted a qualitative descriptive research design using semi-structured in-depth face-to-face interviews. A purposive sampling method was used to recruit eleven patients with cancer who underwent HSCT at an adult oncology center in Saudi Arabia. The interview guide was developed by the authors based on the multi-dimensional health-related QOL model. Participants were asked about their daily activities, problems with coping, quality of life, and personal stress/worries about the future. Data collection was ceased when thematic saturation was reached. Inductive thematic analysis was conducted by two research team members.Results: Seven male and four female participants were interviewed (range of age 18 to 51 years). Interviews lasted between 60 and 75 minutes. Five major themes emerged in this study. The first was Physical Well-Being based on four sub-themes: independence, self-efficacy, health outlook (health perception), and pain. The second theme was Psychosocial Impact based on the subthemes: stigmatization, depression, and social strains. The third and fourth themes were Social Support and Coping with the Disease, with the subthemes: avoidant coping, meditation and faith. The fifth theme included psychosocial/physical stability and optimism.Conclusion: Exploring the lived experiences of cancer survivors can inform supportive health care management. Patients who underwent HSCT reported a series of challenges at the physical, psychosocial, and social levels. Further quantitative research studies are recommended to confirm the impact of HSCT on the QOL of cancer survivors in the Saudi Arabian context.Keywords: stem cell, quality of life, transplantation, survivors, qualitative research